Analisis Pembelajaran Daring dengan Aplikasi Video Conference: Studi Kasus di Sebuah Program Studi Universitas Swasta - Kelvin Irawan; Prayonne Adi; I Nyoman Sutapa (Jurnal Titra, 2021)
During this pandemic, many learning activities that were initially carried out face-to-face were replaced with online learning using applications. Several universities in Indonesia have started implementing online learning for students and lecturers from the odd semester of the 2020 academic year to the odd semester of 2021. The work on this final project uses the Technology Acceptance Model (TAM) method which is the method usually used in analyzing the acceptance of a new technology. This study is also used to determine the existence of several variables that will affect user decisions in the acceptance and use of the new technology. This research was conducted by distributing questionnaires to 152 students of a study program at a private university. After all the data has been collected, the researcher will analyze the data descriptively and test the hypotheses that have been made by testing using the Structural Equation Modeling (SEM) method to determine the influence relationship between indicators and latent variables. The results obtained from the study state that the results in this study are used to determine the factors that influence the acceptance of video conference by students of one of the study programs of a private university so that the results of this research can provide information on the results that can be used by the study program of a private university in knowing factors of student interest in online learning and maximizing the use of video conferencing.